Stick together! - Montijo, Rhode; Reynolds, Luke, 1980- (Montijo, Rhode. Gumazing gum girl!, 2021)
When Gabby Gomez's substitute teacher transforms into a giant hamster monster, she needs help from new friends and old to stop him.